Early-Life Stress Paradigm Transiently Alters Maternal Behavior, Dam-Pup Interactions, and Offspring Vocalizations in Mice - Heun-Johnson, Hanke; Levitt, Pat (Frontiers in Behavioral Neuroscience, 2016)
Animal models can help elucidate the mechanisms through which early-life stress (ELS) has pathophysiological effects on the developing brain. One model that has been developed for rodents consists of limiting the amount of bedding and nesting material during the first postnatal weeks of pup life. This ELS environment has been shown to induce ‘abusive’ behaviors by rat dams towards pups, while mouse dams have been hypothesized to display ‘fragmented care’. Here, as part of an ongoing study of gene-environment interactions that impact brain development, we analyzed long observation periods of wild-type C57Bl/6J dams, with wild-type and heterozygous pups for the Met receptor tyrosine kinase, which is involved in cortical and hippocampal synaptogenesis. Dams with limited resources from postnatal day (P)2 to P9 preserved regular long on-nest periods, and instead increased the number of discrete dam-pup interactions during regular off-nest periods. Immediately after dams entered the nest during off-nest periods in this ELS environment, pups responded to these qualitatively different interactions with an increased number of ultrasonic vocalizations (USV) and audible vocalizations (AV), communication signals that have been associated with aversive and painful stimuli. After returning to control conditions, nest entry behaviors normalized, and dams did not show altered anxiety-like or contextual fear learning behaviors after pup weaning. Furthermore, female mice that had undergone ELS as pups did not show atypical nest entry behaviors in control conditions in adulthood, suggesting that these specific maternal behaviors are not learned during the ELS period. The results suggest that atypical responses of both mother and pups during exposure to this ELS environment likely contribute to long-term negative outcomes in mice, and that these responses more closely resemble the effects of limited bedding on rat dams and pups than was previously suggested. Discerning how different early-life stressors mediate changes in maternal-pup interactions can help elucidate the mechanisms of ELS on brain development and behavior.